Rhythmic auditory stimulation to improve gait rehabilitation outcomes for children with acquired brain injury: a pilot study. (2nd March 2023) - Kelly, Gemma; Pool, Jonathan; Hamilton, Colin; Rodda, Jill
Abstract : Background/Aims: Children with severe acquired brain injury frequently have walking rehabilitation goals. The aim of this study was to investigate if rhythmic auditory stimulation would improve walking speed and gait quality in children with acquired brain injury. Methods: A total of four children were included in this study (age 10–12 years; mean time since acquired brain injury 12.75 weeks). A multiple baseline single case experimental study design was followed. The baseline phase (phase A) consisted of standard rehabilitation (10 physiotherapy sessions a week) and for the intervention phase (phase B), two out of the 10 sessions were replaced with rhythmic auditory stimulation. A 10-metre walk test and the Edinburgh Visual Gait Score was completed twice a week at the beginning and end of the session. Visual analysis of level, slope and trend, and statistical analysis of effect size (Tau-U) was conducted across phases. Descriptive analysis of within-session change was completed. Results: All children showed improvement. In the 10-metre walk test, three children demonstrated a steeper trendline in phase A and one child demonstrated consistent trendlines between phases A and B. Tau-U indicated a small effect size (−0.207 (z =−1.32, P =0.1853)) that was not statistically significant for the Edinburgh Visual Gait Score; one child showed a steeper trendline in phase A and one in phase B, while others were consistent. One child's Edinburgh Visual Gait Score improved greatly in phase B. Tau-U indicated a large effect size (−0.6235 (z=−3.9981, P =0.0001)) that was statistically significant. Within session changes indicated that, overall, children showed greater immediate changes with the Edinburgh Visual Gait Score and 10-metre walk test with the rhythmic auditory stimulation than with standard physiotherapy. Conclusions: In addition to standard physiotherapy, rhythmic auditory stimulation may be of benefit to children relearning to walk after an acquired brain injury, potentially having a greater effect on gait biomechanics than walking speed. Rhythmic auditory stimulation can be considered alongside other gait interventions, but more research is required.